Harry Freedman, The Murderous History of Bible Translations: Power, Conflict and the Quest for Meaning (London – Oxford – New York – New Delhi – Sydney: Bloomsbury 2016) - Wardęga, Jakub (The Biblical Annals, 2018)
Book review: Harry Freedman, The Murderous History of Bible Translations: Power, Conflict and the Quest for Meaning (London – Oxford – New York – New Delhi – Sydney: Bloomsbury, 2016). Pp. 248, £ 20. ISBN 978-1-4729-2167-3 DOI: https://doi.org/10.31743/ba.2018.8.1.07